2020
DOI: 10.1038/s41598-020-68426-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel and green NiFe2O4/geopolymer nanocatalyst based on bentonite for synthesis of imidazole heterocycles by ultrasonic irradiations

Abstract: Geopolymers as aluminosilicate inorganic polymers and eco-friendly building materials which can be used as substrate for different kinds of composite. In this research, according to the fabrication of geopolymer based on bentonite as a substrate and embedment of nife 2 o 4 nanoparticles in the construction of this polymer, the synthesis of a new magnetic nanocomposite (nife 2 o 4 /geopolymer) was investigated for the first time. In order to describe its chemistry and morphology features, different analyses suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Further weight loss of 5 % (w/w) was also observed in the temperature range of 120-700 ℃ which can be attributed to the removal of water from the dihydroxylation process [23]. It can also be attributed to the destruction of carbonate which existed in the structure of iron that is present in the nanoparticle [24]. The temperature above 700 ℃ reveals a more stable sample which indicates that the bentonite-supported Fe-Co-Ni trimetallic nanoparticles are a high-temperature-stable catalyst.…”
Section: Characterization and Physicochemical Properties Of Biodieselmentioning
confidence: 92%
“…Further weight loss of 5 % (w/w) was also observed in the temperature range of 120-700 ℃ which can be attributed to the removal of water from the dihydroxylation process [23]. It can also be attributed to the destruction of carbonate which existed in the structure of iron that is present in the nanoparticle [24]. The temperature above 700 ℃ reveals a more stable sample which indicates that the bentonite-supported Fe-Co-Ni trimetallic nanoparticles are a high-temperature-stable catalyst.…”
Section: Characterization and Physicochemical Properties Of Biodieselmentioning
confidence: 92%
“…Hajizadeh et al reported the preparation of NiFe 2 O 4 /geopolymer nanocatalyst for the synthesis of imidazole derivatives [22]. The three‐component reaction of benzil, benzaldehyde, and ammonium acetate under ultrasound irradiation in the presence of 0.03 g catalyst ensued the anticipated product in 91% yield when ethanol was used as the solvent (Scheme 6).…”
Section: Classificationmentioning
confidence: 99%
“…Geopolymers and magnetic geopolymers have also been proposed as low-cost, effective catalysts for environment governance by “end-of-pipe” treatments, such as photocatalytic degradation of dye wastewater or gas purification and have been employed for hydrogen and biodiesel production as well as in green heterogeneous catalytic processes [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%